Sleep in Offspring of Parents With Mood Disorders - Wescott, Delainey L.; Morash-Conway, Jessica; Zwicker, Alyson; Cumby, Jill; Uher, Rudolf; Rusak, Benjamin (Frontiers in Psychiatry, 2019)
Background: Sleep problems in childhood are an early predictor of mood disorders among individuals at high familial risk. However, the majority of the research has focused on sleep disturbances in already diagnosed individuals and has largely neglected investigating potential differences between weeknight and weekend sleep in high-risk offspring. This study examined sleep parameters in offspring of parents with major depressive disorder or bipolar disorder during both weeknights and weekends. Methods: We used actigraphy, sleep diaries, and questionnaires to measure several sleep characteristics in 73 offspring aged 4-19 years: 23 offspring of a parent with major depressive disorder, 22 offspring of a parent with bipolar disorder, and 28 control offspring. Results: Offspring of parents with major depressive disorder slept on average 26 min more than control offspring on weeknights (95% confidence interval 3 to 49 minutes, p = 0.027). Offspring of parents with bipolar disorder slept on average 27 min more on weekends than weeknights compared to controls, resulting in a significant family history by weekend interaction (95% confidence interval 7 to 47 minutes, p = 0.008). Conclusions: Sleep patterns in children and adolescents were related to the psychiatric diagnosis of their parent(s). Future follow-up of these results may clarify the relations between early sleep differences and the risk of developing mood disorders in individuals at high familial risk.